CoFe2O4-SiO2 Composites: Preparation and Magnetodielectric Properties. (21st September 2016) - Ramesh, T.; Bharadwaj, S.; Murthy, S. R.
Abstract : Cobalt ferrite (CoFe2 O4 ) and silica (SiO2 ) nanopowders have been prepared by the microwave hydrothermal (M-H) method using metal nitrates as precursors of CoFe2 O4 and tetraethyl orthosilicate as a precursor of SiO2 . The synthesized powders were characterized by XRD and FESEM. The (100 - x ) (CoFe2 O4 ) + x SiO2 (where x = 0%, 10%, 20%, and 30%) composites with different weight percentages have been prepared using ball mill method. The composite samples were sintered at 800°C/60 min using the microwave sintering method and then their structural and morphological studies were investigated using X-ray diffraction (XRD), Fourier transformation infrared (FTIR) spectra, and scanning electron microscopy (SEM), respectively. The effect of SiO2 content on the magnetic and electrical properties of CoFe2 O4 /SiO2 nanocomposites has been studied via the magnetic hysteresis loops, complex permeability, permittivity spectra, and DC resistivity measurements. The synthesized nanocomposites with adjustable grain sizes and controllable magnetic properties make the applicability of cobalt ferrite even more versatile.